Exploring Challenges in Integrating ICT in Secondary Mathematics with TPACK - Dorian Stoilescu (SEAMEO Regional Centre for QITEP in Mathematics, 2014)
This paper describes challenges encountered by three experienced secondary mathematics teachers when they try to integrate ICT in their classrooms. This study is based on the four dimension framework developed by Niess: 1) overarching conceptions of integrating ICT, 2) knowledge of instructional strategies and representations for teaching, 3) knowledge of students’ knowledge of technology; and 4) knowledge of curriculum and curriculum materials that integrate technology with learning. By using this analysis, we explore the challenges that teachers face on each of the four levels of integration ICT and suggest waysof improving these strategies in mathematical instruction.